Controllable fabrication of a super broadband antireflection film: Gd: MgO nanoparticles composite film by pulsed laser deposition method. (August 2021) - Wang, Mengjia; Wang, Xuemin; Yin, Hongbu; Xiao, Tingting; Yang, Qi; Li, Jia; Jiang, Tao; Wang, Xinming; Wu, Weidong
Abstract: A series of Gd nanoparticles (NPs): MgO composite films with different Gd contents were prepared using pulsed laser deposition (PLD) method. The state of Gd element was confirmed by X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analysis. Transmission electron microscopy (TEM) images show that Gd NPs were uniformly embedded in a single crystal MgO film and formed a subwavelength microstructure. Ultraviolet–visible (UV–vis) spectra show that the transmittance of the samples first increased and then decreased with the increase in the number of laser pulses focused on Gd target from 50 to 800. The highest transmittance of 88.6% (1000–1900 nm) was obtained at a pulse number of 200. The transmittance of all the samples is higher than that of MgO substrate (86.8%, 1000–1900 nm), i.e., a super broadband antireflection phenomenon is observed, and the maximum antireflection wavelength ranges from 500 nm to 2500 nm. This can be explained by effective medium theory (EMT). In this study, super broadband antireflection based on the microstructure formed by embedding NPs in homoepitaxial films is reported. Highlights: A series of Gd: MgO nanoparticles composite films were fabricated by PLD. The super broadband antireflection phenomenon is reported. A subwavelength microstructure was formed by embedding Gd NPs in MgO film. The structure is equivalent to the multilayer films with graded refractive index. The antireflection performance can be adjusted by regulating the content of Gd.